Multiculturalism on the Back Seat? Culture, Religion, and Justice - Maclure, Jocelyn (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Alan Patten’s Equal Recognition is a major contribution to the normative literature on minority rights. I nonetheless suggest that liberal culturalism as a normative theory, even in Patten’s sophisticated version, is ill suited to deal with the challenges related to the status of religion in the public sphere that are so prevalent in contemporary democracies. In addition, I submit that Patten did not supply a fully convincing answer to the argument that liberal egalitarianism, well understood, is capacious enough to secure fair terms of social cooperation for members of cultural minorities, making the (allegedly burdensome) language of “cultural rights” and “cultural recognition” superfluous.